Aviation maintenance technician series. - Crane, Dale (Crane, Dale. Aviation maintenance technician series., 2018)
Dale Crane's Aviation Maintenance Technician Series is the essential resource to pass the FAA Knowledge Exams for Aviation Maintenance Technicians. This volume of the series covers the AMT ""Powerplant"" section of the curriculum.